A Rare Case of Completely Healed Pneumomediastinum Due to Asthma Exacerbation in A Young Male Patient - Tarigan, Amira Permatasari; Pandia, Pandiaman; Pradana, Andika; Hutabarat, Eva Susanti Debora; Ramadhani, Adini Arifah (Respiratory Science, 2024)
Background: The term pneumomediastinum (PNM) refers to the presence of air within the mediastinal cavity. This illness is uncommon but can arise in adolescents with severe asthma attacks. In children aged 5 to 34, the incidence of pneumomediastinum after an acute asthma attack is 1 in 25,000. Men made up the majority of patients (76 percent of all cases). Pneumomediastinum can be diagnosed with the assistance of a chest CT scan. Case: A young man was diagnosed with pneumomediastinum due to an acute asthma attack in this case report. Symptoms of uncontrolled asthma include shortness of breath that worsens with wheezing, chest tightness, and a nonproductive cough. Since the age of 12, the patient in this instance has been receiving salbutamol inhalers. The physical examination revealed polyphonic lung respiration and subcutaneous crepitus in the neck, shoulders, and anterior chest. With adequate management of an asthma episode, pneumomediastinum recovers spontaneously, followed by recurrent symptomatic status, physical examination, and radiography examination. Discussion: Acute asthma exacerbations are one of the factors that can lead to spontaneous pneumomediastinum, in which mediastinal air can permeate the tissue and generate a pneumothorax, and if there is air in the subcutaneous area, it can lead to subcutaneous emphysema. Conclusion: Pneumomediastinum was a rare incidence, pulmonologists examining young adults with acute asthma exacerbations should evaluate for pneumomediastinum. In usual asthma therapy, a chest CT-scan is essential to screen for pneumomediastinum.